Origin and Function of Circulating Plasmablasts during Acute Viral Infections - Fink, Katja (Frontiers in Immunology, 2012)
Activated B cells proliferate and differentiate into antibody-producing cells, long-lived plasma cells and memory B cells after immunization or infection. Repeated encounter of the same antigen triggers the rapid re-activation of pre-existing specific memory B cells, which then possibly enter new germinal center reactions and differentiate into short-lived plasmablasts or remain in the system as memory B cells. Short-lived plasmablasts appear in the circulation transiently and the frequency of these cells can be remarkably high. The specificities and affinities of single plasmablasts have been reported for several viral infections, so far most extensively for influenza and HIV. In general, the immunoglobulin variable regions of plasmablasts are highly mutated and diverse, showing that plasmablasts are derived from memory B cells, yet it is unclear which memory B cell subsets are activated and whether activated memory B cells adapt or mature before differentiation. This review summarizes what is known about the phenotype and the origin of human plasmablasts in the context of viral infections and whether these cells can be predictors of long-lived immunity.